The State: A Theoretical Evaluation on the Axis of Political Sociology - Bayezit, Galip; Tan, Mehmet (Fırat University, 2023)
Today, the debates on the state phenomenon mostly revolve around the nation-state and global system projects. In this study, the phenomenon of the state is discussed in the context of political sociology, in the axis of politics-society relationship. The concept of nation-state and global politics; international political-economic structures and their effects are discussed within the framework of global policies and the collapse of empires. In this context, “Is it the end of the nation-state?”, “Is there a future for the nation-state at a time when national governments cannot control their own economies?”, “Is an unlimited world state possible in a world where information technologies are advancing at a dizzying pace?” The answers to these questions were sought by considering the current situation. In the final analysis, the idea of an unlimited world state is just a myth; The biggest obstacle to this project is the idea of the nation-state and "nationalism", which is still one of the most influential currents of thought; because it has been understood that a world politics that ignores national-spiritual values, nation and national culture is not possible.

Günümüzde devlet olgusu üzerine yapılan tartışmalar büyük oranda ulus-devlet, küresel sistem projeleri etrafında dönmektedir. Bu çalışmada, devlet olgusu siyaset sosyolojisi bağlamında, siyaset-toplum ilişkisi ekseninde ele alınmaktadır. Ulus-devlet ve küresel siyaset kavramı; uluslararası siyasî-ekonomik yapılanmalar ve etkileri, küresel politikalar ve imparatorlukların çöküşü çerçevesinde tartışılmaktadır. Bu kapsamda “ulus-devletin sonu mu”, “ulusal hükümetlerin kendi ekonomilerini kontrol edemediği bir dönemde ulus-devletin bir geleceği var mı”, “bilişim teknolojilerinin baş döndürücü bir hızda ilerlediği bir dünyada sınırsız bir dünya devleti mümkün mü” sorularına günümüzdeki durum göz önünde bulundurularak cevap aranmaktadır. Son tahlilde, sınırsız dünya devleti fikrinin bir efsaneden ibaret olduğu; bu projenin önündeki en büyük engelin ulus-devlet ve hâlen en etkili düşünce akımlarından olan “milliyetçilik” fikrinin olduğu; millî-manevî değerleri, milleti ve millî kültürü yok sayan bir dünya siyasetinin mümkün olmadığı anlaşılmaktadır.
DEVLET: SİYASET SOSYOLOJİSİ EKSENİNDE KURAMSAL BİR DEĞERLENDİRME
Keywords: Political Science (Other); Siyaset Bilimi (Diğer)